Rural Poverty Alleviation in Brazil : Toward an Integrated Strategy - World Bank (Washington, DC, 2013)
The objective of this report is to design an integrated strategy for rural poverty reduction in Brazil. It contains an updated and detailed profile of the rural poor in the northeast and southeast regions of Brazil; identifies key determinants of rural poverty in these regions; and proposes a five-pronged strategic framework and a tentative set of policy options. The latter were identified via an analysis of rural poverty determinants complemented with an evaluation of relevant current public programs and six in-depth thematic studies: (a) the dynamics of the Brazilian small farm sector, (b) rural labor markets, (c) rural land markets, (d) rural non-farm employment, (e) rural education, and (f) rural pensions.